A common founder for the 35delG GJB2gene mutation in connexin 26 hearing impairment. Issue 8 (1st August 2001) - Van Laer, L; Coucke, P; Mueller, R F; Caethoven, G; Flothmann, K; Prasad, S D; Chamberlin, G P; Houseman, M; Taylor, G R; Van de Heyning, C M; Fransen, E; Rowland, J; et al.
Abstract : Fifty to eighty percent of autosomal recessive congenital severe to profound hearing impairment result from mutations in a single gene, GJB2, that encodes the protein connexin 26. One mutation of this gene, the 35delG allele, is particularly common in white populations. We report evidence that the high frequency of this allelic variant is the result of a founder effect rather than a mutational hot spot in GJB2, which was the prevailing hypothesis. Patients homozygous for the 35delG mutation and normal hearing controls originating from Belgium, the UK, and the USA were genotyped for different single nucleotide polymorphisms (SNPs). Four SNPs mapped in the immediate vicinity of GJB2, while two were positioned up to 76 kb from it. Significant differences between the genotypes of patients and controls for the five SNPs closest to GJB2 were found, with nearly complete association of one SNP allele with the 35delG mutation. For the most remote SNP, we could not detect any association. We conclude that the 35delG mutation is derived from a common, albeit ancient founder.